(3eLdI GdaJM (B/s (3UMjaI ESdGejI YdejI CNdGbjI , CUOQgG eMH GdOjf GdNWjH (B.s ((3GdbGgQI (B- (3eUQ (B:s, 1926)
(3aj GdOjf GdESdGej(B.s
(3eJhbaI Yf GdUOhQ(B.s
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
Keywords: (3GdESdGes -- (3OhQjGJs